IMPLEMENTASI KEPEMIMPINAN PROFETIK DI ERA NEW NORMAL - Darda Mustopa, Adi Supardi (As-Salam: Jurnal Studi Hukum Islam & Pendidikan, 2021)
AbstrakThis research is to find out the implementation of leadership in Indonesia in the new normal era with the approach of prophetic character values of the prophet Muhammad saw. Data analysis is done through description on the prophetic properties of the prophet Muhammad saw. Methods are conducted through descriptive qualitatives, with empirical data and library studies. That the leaders needed by the People of Indonesia can be categorized as 4 types, 1), loved leaders; 2), a trustworthy leader; 3), guiding leader; and 4) personality through transformational, visionary nature and high work ethic. This research can contribute as information characteristics of leaders that people want in the new normal era today.